1999
DOI: 10.1017/s0022112099004723
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of stability and transition in high-speed wakes

Abstract: The investigation undertaken deals with the development of disturbances in a supersonic wake (free viscous layer and regular wake) behind a flat plate both in its linear and nonlinear stages. The influence of a number of factors (Mach and Reynolds numbers, temperature factor, thickness of the plate, length of its stern) on the wake stability and transition was studied. The development of the artificial disturbances in a wake at Mach number M∞ = 2 was investigated also.It was found that compressibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…In the compressible turbulent wake behind the turbulent boundary layers, Gai et al (2002) visualized weak periodical large-scale inclined structures. Lysenko (1999) showed the development of three-dimensional disturbances in the supersonic wake of a at plate with a stern. A complete quantitative description of the underlying mechanism of a compressible wake that links to three-dimensional behavior in incompressible wakes and the resultant structures awaits DNS studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the compressible turbulent wake behind the turbulent boundary layers, Gai et al (2002) visualized weak periodical large-scale inclined structures. Lysenko (1999) showed the development of three-dimensional disturbances in the supersonic wake of a at plate with a stern. A complete quantitative description of the underlying mechanism of a compressible wake that links to three-dimensional behavior in incompressible wakes and the resultant structures awaits DNS studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear why the observed oblique perturbation undergoes the largest growth. It could be related to one of the following reasons: (i) the growth of the most unstable oblique mode, as found by Papageorgiou (1990); (ii) as hypothesized by Lysenko (1999), a receptivity of an inclined symmetric mode which emerges for Ma r > 1.2 (Watanabe & Maekawa 2004); (iii) a secondary acoustic mode which resonates between the sonic lines of the wake as in the boundary layer (Mack 1990); or (iv) a triadic nonlinear interaction as observed in the H-type transition in the boundary layer (Hebert 1988). The debate surrounding the origin of the three-dimensional modes remains open and central to the understanding of the transitional mechanism of the planar wake.…”
mentioning
confidence: 89%
“…This result was nuanced by Papageorgiou (1990) who questioned the validity of the parallel flow assumption inherent in the temporal stability calculations and showed that a three-dimensional wave inclined at 60 • has the highest growth rate for spatially evolving wakes with a Gaussian velocity profile at Ma ∞ = 3.0. The obliquity of the transitional mode was experimentally observed by Lysenko (1999) by artificially forcing a splitter-plate wake at Ma ∞ = 2.0. It is unclear why the observed oblique perturbation undergoes the largest growth.…”
mentioning
confidence: 99%
“…Известно, что увеличение числа Маха оказывает стабилизирующий эффект на течение в свободных слоях смешения и спутных следах (например, [1]). Естественно предположить, что относительно длин-ный свободный слой смешения, сформированный около обтекаемой поверхности, может уменьшить темпы роста и подавить возмущения второй моды, имеющие короткую длину волны (порядка двух толщин пограничного слоя).…”
Section: поступило в редакцию 9 марта 2017 гunclassified